Staphylococcus aureus Avoids Autophagy Clearance of Bovine Mammary Epithelial Cells by Impairing Lysosomal Function - Geng, Na; Wang, Xiaozhou; Yu, Xiaohui; Wang, Run; Zhu, Yiran; Zhang, Meihua; Liu, Jianzhu; Liu, Yongxia (Frontiers in Immunology, 2020)
In dairy herds, mastitis caused by Staphylococcus aureus (S. aureus) is difficult to completely cure on the account that S. aureus can invade bovine mammary epithelial cells (BMECs) and result in persistent infection in the mammary gland. Recent studies have demonstrated that autophagy can participate in cell homeostasis by eliminating intracellular microorganisms. The aim of the study was to investigate why S. aureus can evade autophagy clearance and survive in BMECs. The intracellular infection model was first constructed, then the bacteria in autophagosome was detected by transmission electron microscopy. The autophagy flux induced by the S. aureus was also evaluated by immunoblot analysis and fluorescent labeling method for autophagy marker protein LC3. In addition, lysosomal alkalization and degradation ability were assessed using confocal microscopy. Results showed that, after infection, a double-layer membrane structure around the S. aureus was observed in BMECs, indicating that autophagy occurred. The change in autophagy marker protein and fluorescent labeling of autophagosome also confirmed autophagy. However, as time prolonged, the autophagy flux was markedly inhibited, leading to obvious autophagosome accumulation. At the same time, the lysosomal alkalization and degradation ability of BMECs were impaired. Collectively, these results indicated that S. aureus could escape autophagic degradation by inhibiting autophagy flux and damaging lysosomal function after invading BMECs.